Modelling price scenarios for sustainable collective action and farm production: Pepper in El Roble settlement, Costa Rica - Miranda Montes, Donald (2015)
Pepper (Piper nigrum L.) is considered a non-traditional cash crop for enhancing local development in Costa Rica and a suitable activity for small farmers. Trade of pepper has been done by using contractual agreements between producers and processors, which provides at least three functions: insurance, incentives and information. Contracts also require a high level of commitment from contracting parties to keep the equity, efficiency, and sustainability of the trade relationship. The shift of trade conditions from a competitive to a monopsony market encouraged a group of farmers to start an association that aims to bulk and process pepper from members. Breaching contracts by members of the association endanger this effort of sustainable entrepreneurship. This usually happens when temporary market conditions yield higher procurement prices by other competitors. This situation is also worsened by the lack of proper information on production and processing costs between the contracting parties, and then, the disagreement on the procurement price fixation and payment conditions. By using a mixed integer linear optimization model, we aim to identify the 'best' price of fresh pepper traded between both parties. We make use of primary information from 12 different farms on production costs and from the association on processing costs. The model incorporates minimum required net margins for all contracting parties, while modelling the net margins of each party, the amount of traded fresh pepper and preferred contract possibilities, given different fresh pepper price scenarios. At lower prices, some of the farmers that supply pepper, do this to just break-even. At higher prices, more is supplied by more farmers. Under monopsony conditions and individual contracts between parties, it is in the interest of the buyer to offer higher fresh pepper prices in order to buy and process more pepper, up to the point that the marginal costs of buying more pepper are equal to the marginal benefits of that extra pepper. This is because the processor has fixed costs, next to variable costs. Higher volumes reduce the average total costs of processing per kg of pepper, and thereby increase profit. When group contracts are possible, thus under bilateral monopoly conditions - farmers acting as 'one' seller and the processor as the only buyer - more fresh pepper is supplied at higher prices than under monopsony conditions as more farmers would have higher surpluses. At the same time the processor would have a higher profit than using individual contracts.